Private Landlords and Redevelopment: "The Ward" in Toronto, 1890-1920 - Dennis, Richard (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1995)
Drawing on contemporary accounts of inner-city slums and on an analysis of assessment roll data, this paper examines patterns of speculation, property exchange, improvement and redevelopment in "The Ward" in Toronto, contrasting the depression of the 1890s with the return of boom conditions prior to World War I. It is argued that contemporary critiques of speculative landlords hoarding land and neglecting the maintenance and improvement of existing buildings while they waited for land values to increase, were an oversimplification of a much more complex reality. During the property boom of the early 1900s most sites changed hands at least once, partly reflecting the desire of recent immigrants to obtain property. There were also differences in the attractiveness of the land, and hence the rate of increase in its value, and the pressure for redevelopment of different parts of "The Ward". There were also differences over time, not only between the 1890s depression and the 1900s boom, but also between the 1900s and the mid-1910s, when the Bureau of Municipal Research reported on the area. Nor was it likely, given the continuing demand for accommodation among a rapidly increasing population, that landlords were, as they claimed, failing to make profits from renting out poor-quality dwellings and stores. In this respect, the experience of turn-of-the-century Toronto contrasted with the "rent gap" hypothesis used by urban geographers to account for the redevelopment of neglected inner-city neighbourhoods during more recent property booms.